Microwave Absorption: Confining Tiny MoO2 Clusters into Reduced Graphene Oxide for Highly Efficient Low Frequency Microwave Absorption (Small 30/2020). Issue 30 (28th July 2020) - Wu, Cao; Chen, Zhaofeng; Wang, Meiling; Cao, Xun; Zhang, Yong; Song, Pin; Zhang, Tianyuan; Ye, Xinli; Yang, Yong; Gu, Weihua; Zhou, Jiadong; Huang, Yizhong
Abstract : In article number 2001686, Zhaofeng Chen, Meiling Wang, Jiadong Zhou, Yizhong Huang, and co‐workers realize uniform MoO2 clusters sandwiched between porous carbon shells and RGO support by a supermolecular cage‐confinement pyrolysis route. The introduction of crosslinkers into hydrogel precursors have remarkable adjustment effects on low‐frequency electromagnetic wave absorption traits.